Characterization of Activated Charcoal from Pyrolysis Of Human Hair Cutting and Its Utilization as an Adsorbent - Adnyani, Dewa A.A.R.S; Anom, I Dewe Ketut; Lombok, Johny (Jurnal Kimia Fullerene, 2025)
This study aims to determine the characteristics of activated carbon from human hair cutting waste and to determine its ability to adsorb metals contained in water. This study uses an experimental method that is preceded by the activation of charcoal with KOH activator. Then continued with characterization using Fourier Transform Infra - Red (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope Energy Dispersive X-Ray (SEM-EDS) and Atomic Absorption Spectrophotometer (AAS). The results of the study showed that the FTIR spectrum showed the presence of a groupOH, CH, C=C and CO. The results of SEM analysis of activated carbon show the morphology of the pores of unactivated carbon, namely the surface looks smooth and dense with small particles evenly distributed and there are no large pores or significant cracks. Activated carbon from activation with KOH has a surface structure that looks more porous than before activation. The results of EDS analysis show the elemental composition of unactivated carbon and after activation using KOH only the C element is produced. XRD analysis of unactivated activated carbon shows one wide and not sharp diffraction peak. This characteristic indicates that the material has an amorphous structure, which means that the atoms in the material are not arranged crystalline but randomly. The relatively low diffraction intensity and high background strengthen the amorphous character of this pyrolysis carbon. After activation using KOH, the diffraction pattern still shows a wide peak at the same 2θ, but with higher intensity and a more defined peak shape. The results of AAS analysis show that activation with KOH provides high adsorption efficiency of 26.82%.